The effects of biopolymers composite based waste cooking oil and titanium dioxide fillers as superhydrophobic coatings - Marsi, N.; M Rus, A Z
This project presents the effect of biopolymer composite surface coating on TiO2 fillers by analysing the static water contact angle, SEM micrographs, porosity, density and refractive index of biopolymer doped with different loading of TiO2. The different ratio loading of 0.5, 1.0, 1.5, 2.0 and 2.5 (wt/wt%) TiO2 can be used to improve the material properties in practical use for outdoor application especially to enhance the stability of surface coating. It is found that the smooth surfaces with a low ratio loading of TiO2 fillers on biopolymer composite surface coating increases the static water contact angle up to 162.29°. It is interpreted with respect to nano- features existing on the surface of the water repellent creates a thin superhydrphobic layer. The relationship between porosity and density is indirectly proportional where the higher the loading of TiO2 filler produce the lower porosity up to 0.86% of the surface coating. The movement from shorter to longer of wavelength was observed before and after exposure indicates that there are optimization of absorption of UV-B radiation as the amount of delocalisation.